Systems Thinking for Sustainability Education in Building and Business Administration and Management Degrees - Marcos-Sánchez, Rafael; Ferrández, Daniel; Morón, Carlos (Sustainability, 2022)
In 2015, the United Nations set the 2030 Agenda, which established 17 Sustainable Development Goals (SDGs) including different areas—among them, Education—which determine the reality and the future of new generations. The data of SDG24 2021 establish that, by 2030, the reference values will be below those expressed in SDG 4. Education for sustainable development poses a series of competencies to achieve it; the challenge for teachers is to develop strategies, tools and methodologies that enable meaningful learning for the required complexity. Managing and solving sustainability problems requires people with systemic competences who are able to see the whole in the individuality, presenting a breadth of vision for a complex world. It is important that training takes place in universities so that students are equipped with a holistic understanding of systems. The aim of this research is to propose a didactic proposal for students of the double degree in Building and Business Administration and Management to acquire the competences of systems thinking, interdisciplinary work, personal and inter-collaborative relationships and tolerance to ambiguity and uncertainty using project-based learning and systems simulation. To achieve this, a classroom intervention proposal has been designed for the subjects Strategic Management and Sustainable Building in the fourth year of the double degree using the project-based learning and systems thinking. This practical proposal allows participants to develop a holistic view of the problems, enhancing the capacity for systemic and sustainable resolution in the design of more sustainable building systems, as well as promoting training in strategic decision making in environmental management in the medium and long term.